Diagnóstico de las expresiones de cultura artística en la universidad técnica de Cotopaxi como parte de la formación integral. Propuesta de organización y funcionamiento de un centro especializado universitario. - Valdez Rodríguez, José Elías (2016)
The research study will revitalize the expressions of artistic culture artistic at Technical University of Cotopaxi, focusing on the Culture content and memory; Expressions of culture artistic, Integral Training, Organization and Operation of a Specialized Center of Culture, this research project corresponds to the feasible project, that means, it is based on bibliographic and field research, and a proposal for intervention. The population will be 320 people who are in first cycles of a major by Academic Unit, such as: Social Communication, Graphic Design, Ecotourism, Physical Culture Center, Gymnastics students, their teachers of each major and university authorities who are engaged in Cultural Identity, Folklore or related on it, the sample will be of 178 employees, data that was obtained after performing the calculations of sampling. It was determined that if it is positive strengthen the university culture as an academic process, its influence to the external sector will improve the link and undertake the design of a specialized center for its operation, it considered the hypothesis and people requested that it will design the creation of a specialized center of culture. After obtaining the results it is identified an interest for the expressions of artistic culture in dance, theater, music, painting, poetry that will improve the integral training of the university students, the beneficiaries will be the students of first cycles of all major at UTC, with projection to keep all university major as part of its integral and complementary training, other beneficiaries will be university staff and teachers, administrative personnel and employees, external community including children, youth and adults in general.